The Labor Market Effects of Financial Crises : The Role of Temporary Contracts in Central and Western Europe - Sharma, Siddharth; Winkler, Hernan (World Bank, Washington, DC, 2017)
This paper examines how the 2008-09 financial crisis affected labor markets in Central and Western Europe, and how this impact depended on employment protections laws. Using a differences-in-differences approach that compares industries with varying degrees of inherent dependence on external financing, the analysis finds that the crisis had significant negative impacts on employment, particularly on temporary, less skilled, and younger workers. These impacts on the level and composition of employment were significantly stronger in countries with stronger legal protection of permanent workers from dismissal. This finding suggests that, given regulatory inflexibility in adjusting the permanent workforce, firms responded to tightening financial constraints by disproportionately laying off temporary workers (who tend to be younger and less skilled than permanent workers).